A Aventura como Ação Política: as Viagens Jangadeiras das Décadas de 1940-1950 - Abreu, Berenice (Trabalhos de Antropologia e Etnologia, 2020)
This article discusses the political action of rafts who ventured into the sea on crossings in the 1940s and 1950s. During this period, three raft trips were made: to Rio de Janeiro, led by Jacaré; to Porto Alegre; and to Buenos Aires, Argentina, led by Mestre Jerônimo. Hemerographic and movie news sources were used in the research, as well as the contents of two diaries written in 1941. We conclude that these political actions were strategies to attract attention to the precarious living and working conditions of raft fishermen and to fight for social rights